Effect of Financial Risk Audit in Light of International Financial Reporting Standard (IFRS) on Credit Decisions (Applied Research at Sumer Commercial Bank) - Jamal Naji Al-Musallamawi; Sabeha Barzan AL - Obeid (Journal of Madenat Alelem University College, 2020)
The past years have witnessed a remarkable development in bank credit activity, after the ‘expansion of various business activities and projects in a qualitative and geographical manner and increasing the need to finance them, leading to the achievement of expansion targets or the start of new projects. This research focuses ‘on highlighting the impact of financial risk auditing in the light of International Financial Reporting Standards on credit decisions. The problem lies in the absence of a financial risk audit program under the application of IFRS in Iraqi private commercial banks helps to provide sufficient information on financial risks that are accurate, reliable and Comparable and contribute to the improvement of the Department’s credit decisions, The aim of the study is to highlight the importance of audit financial risk disclosure in accordance with IFRS and to identify the types of credit risk faced by private commercial banks in the Iraqi environment (sample of which is Gulf Commercial Bank) The researchers reached a number of conclusions, most notably the application of some IFRS in private commercial banks listed on the Iraqi market for securities and also partial application, not full application. Accordingly, the researchers proposed a number of recommendations, most notably the full compliance with the application of IFRS when preparing the financial statements in the Iraqi private banks listed in the Iraqi Stock Exchange and follow up their application and the sectoral body overseeing the activity of private banks to help banks achieve a qualitative leap in the disclosure of Financial risks to raise the level of confidence in management decisions and provide banking services that attract investors to contribute to increase the chances of success and expansion